Ternate Smart City Policy Implementation - Muksin, Isra (Yayasan Sinergi Kawula Muda, 2023)
The implementation of Smart City Policy has been applied in several cities in Indonesia including Ternate City which has been applied since 2017. In its implementation there are still obstacles faced in the form of budget limitations, human resources and community participation. This research aims to find out the implementation of Smart City policy in Ternate City, this research uses descriptive with qualitative approach. The results of the study can reveal several important things related to the implementation of smart city policies such as; First, budget constraints due to budget refocusing factors that occur at almost all levels of government in order to focus on handling covid-19, so that the SPBE master plan draft has not been implemented and internet capacity spending is still small which results in not all areas of Ternate City getting free internet facilities. Second, the aspect of the availability of human resources that are representative and able to become a motor in the movement of smart city policy implementation. Diskomsandi still needs many more experts even though the current Diskomsandi staff are qualified enough for that, but on a further development scale, of course, the Ternate City Communication, Information and Standardization Office really needs more qualified experts. Third, the aspect of the Command Center, the unavailability of Command Center facilities where data related to the implementation of smart city policies can be centralized all at the Ternate City Communication, Informatics and Coding Office.